Pyogenic liver abscess in children: two cases report and literature review - Ferrelli, Regis Schander; Bischoff, Adrianne Rahde; Olsen, Virgílio; Ribeiro, Mariana Rangel; Alves, Daniela Osorio; Dos Santos, Boaventura Antônio (Clinical and Biomedical Research, 2013)
Description of two cases of pyogenic liver abscess. The first case: a 3-years-old immunocompetent girl with fever, abdominal pain, vomiting, and diarrhea. Abdominal ultrasound: multiloculated heterogeneous collection in the right hepatic lobe (Figure 1A). The second case, a 1-year-old girl with congenital neutropenia, showed fever, malaise, anorexia, sweating and pallor. Abdominal computed tomography showed hypodense lesion with heterogeneous impregnation by contrast in the left hepatic lobe (Figure 1B). Different clinical presentations, images and treatment are of special interest in pediatrics and are reviewed in this text.